Design and simulation of a PWM based phase synchronous inverter for utility grid systems with 20km feeder line / Tawfikur Rahman, S. M. A. Motakabber and M. I. Ibrahimy - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, M. I. (Research Management Institute (RMI), 2017)
In recent years, the utility grid system is more essential for the power transmission and distribution system because it cannot produce harmful gases or no discharge waste in the environment. PWM based phase synchronous invert systems are generally utilised in the high efficiency energy supply, long distance and higher power quality. The inverter output voltage depends on the coupling transformer, input sources and invert controllers. An inverter using a three leg IGBT has been designed for utility grid and simulated by using MATLAB2014a. In this paper, both sides of the LCL filters are used for removing the DC ripple current, reducing the noise and synchronous the output phase between inverter and the utility grid. The PWM controller has created pulse signal to control the inverter, electronic switches and precisely synchronise with grid line frequency. In this system, the input DC voltage 500V, switching frequency 1.65 kHz, grid frequency 50Hz, 20 km feeder (resistance, inductance and capacitance per unit length, which are 0.1153, 1.05e-3 and 11.33e-09 ohms/km) with 30MW three phase load (active and inductive reactive power which are 30e6 W and 2e6 var) and also a balanced utility grid load of star configuration (00 , 1200 , and 2400 degree) are considered in the design. On the other hand, three phase transformer consists of three signal phase transformers, normal power 100e3 , magnetization resistance and inductancewhich are 500 pu and 416.67pu are considered in this design. The system conversion efficiency is 99.94% and 99.96%, while the total THD are 0.06% on inverter side and 0.04% on grid side.